Biology of Rove Beetles (Staphylinidae) Life History, Evolution, Ecology and Distribution (Springer International Publishing, 2018)
Rove beetles (Staphylinidae) are common elements of the soil biota, living in the litter and deeper soil layers. Although they are one of the most diverse and speciose groups of insects, no comprehensive books on their general evolution and ecology are as yet available. This book fills that gap, discussing significant aspects and active research examples in the fields of phylogeny and systematics, ecology and conservation, and reproduction and development. The combination of review chapters and case studies provides an excellent introduction to the biology of rove beetles and enables readers to become familiar with active research fields in this megadiverse group of beetles. Offering easy access to these fields, it also demonstrates how staphylinids are used as bioindicators in applied ecosystem research, including that concerning conservation issues. Experienced scientists and beginners alike find the diversity of subjects covered intriguing and inspiring for continuing and starting their own research. The book is intended for students and researchers in biology and zoology (entomology), including morphologists, ecologists, soil scientists, evolutionary biologists, paleontologists, biogeographers, taxonomists and systematists.